3+3=8x+23

Simple and best practice solution for 3+3=8x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+3=8x+23 equation:


Simplifying
3 + 3 = 8x + 23

Combine like terms: 3 + 3 = 6
6 = 8x + 23

Reorder the terms:
6 = 23 + 8x

Solving
6 = 23 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
6 + -8x = 23 + 8x + -8x

Combine like terms: 8x + -8x = 0
6 + -8x = 23 + 0
6 + -8x = 23

Add '-6' to each side of the equation.
6 + -6 + -8x = 23 + -6

Combine like terms: 6 + -6 = 0
0 + -8x = 23 + -6
-8x = 23 + -6

Combine like terms: 23 + -6 = 17
-8x = 17

Divide each side by '-8'.
x = -2.125

Simplifying
x = -2.125

See similar equations:

| (x)(x)-11x+18=0 | | 3/2y-8=-5 | | 7x+20=3x+36 | | 2x+9=2x+3 | | x^2=5y+35 | | 4+3x=6x-83x-12 | | -3x+5(-6x+4)-(-30x+16)=-9(x-5) | | 9k^2+29k+8=0 | | 16x-22x=1/2 | | 6p+11=3p-4 | | 6z-5=3z-4 | | 16x/-22x=1/2 | | X-80=100 | | 6/7y=-18/77 | | 5/7x-3=2 | | -0.1x+4=11 | | 2x-(5x+9)=6(2x+1) | | -2(4x+1)+3x-7=2(x+2)+7x-1 | | 6/7y=18/77 | | y/5-1=0 | | 60x^3-30x^2=o | | 1000=2x+0.5y | | A-99=100 | | 0.7(5x+7)=2.0-(x-3) | | x^2+y^2=81-8x^2-8y^2 | | A+25=56 | | y/3-8=-9 | | 4/3e-1/6=3/5/6 | | 4z=1/3 | | 0=8x^2+44x-24 | | K/3=900 | | 4x-(2x-5)=75 |

Equations solver categories